Striking a balance: Managing El Niño and La Niña in Vietnam’s agriculture - Sutton, William R.; Srivastava, Jitendra P.; Rosegrant, Mark W.; Thurlow, James; Sebastian, Leocardio (World Bank, 2019)
This report’s purpose is to help Vietnam policy makers and stakeholders prepare for future El Niño–Southern Oscillation (ENSO) events. It does this by providing information on ENSO’s agricultural, economic, and poverty impacts in Vietnam and outlining ways forward. The report finds that ENSO’s impacts vary from region to region and harm Vietnam’s people, economy, and agricultural sector. The country prepared for, and responded to, the 2014–2016 El Niño, but there is still room to improve upon these actions. Being proactive to prepare for ENSO is important because of Vietnam’s high exposure to climate shocks, the prominence of the agricultural sector in the national economy, the rural population’s climate vulnerability, and the lack of research on ENSO in Vietnam